1996
DOI: 10.1007/bf00183123
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the rete testis

Abstract: Adenocarcinoma of the rete testis is a rare tumor. Histologic diagnosis is difficult, and in the past the tumor may have been incorrectly identified in a number of cases, leading to misleading information on the nature and behavior of this neoplasm. We present the case of a 39-year-old man with a long history of a small left hydrocele, who was lost to follow-up and presented again 2 years later with testicular discomfort. Sonographic findings were consistent with a testicular tumor. Histology confirmed low-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Their US appearances have not been well described in the literature; we are aware of only one report (148) in which the authors indicated that US findings are consistent with those of other testicular tumors.…”
Section: Miscellaneous Benign and Malignant Testicular Massesmentioning
confidence: 50%
“…Their US appearances have not been well described in the literature; we are aware of only one report (148) in which the authors indicated that US findings are consistent with those of other testicular tumors.…”
Section: Miscellaneous Benign and Malignant Testicular Massesmentioning
confidence: 50%
“…1,9,17 This papillary growth pattern was not seen in this study. A rete testis carcinoma in humans can have features similar to Sertoli cell tumors.…”
mentioning
confidence: 50%
“…24 In humans, the pathologic features of rete testis adenocarcinoma have been well documented by case reports and review articles. 9,17,19 In dogs, Sertoli cell tumors, seminomas, and interstitial cell tumors account for most of the testicular neoplasms. 5,25 These tumors usually have a benign behavior but occasionally metastasize.…”
mentioning
confidence: 99%
“…The majority of patients exhibit hydrocele, and echoic paratesticular regions are observed (3,15,16). Nodular septations with cystic solid components have also been reported as an unusual observation which varies from other pathological tumor types (17). In the majority of cases, the lesions present as hypoechoic masses with poorly-defined borders, although an uneven echo pattern is detected on occasion (3,9).…”
Section: Discussionmentioning
confidence: 97%